Integrin α5β1 nano-presentation regulates collective keratinocyte migration independent of substrate rigidity - Di Russo, Jacopo; Young, Jennifer; Wegner, Julian W. R.; Steins, Timmy; Kessler, Horst; Spatz, Joachim P. (eLife, 2021)
Nanometer-scale properties of the extracellular matrix influence many biological processes, including cell motility. While much information is available for single-cell migration, to date, no knowledge exists on how the nanoscale presentation of extracellular matrix receptors influences collective cell migration. In wound healing, basal keratinocytes collectively migrate on a fibronectin-rich provisional basement membrane to re-epithelialize the injured skin. Among other receptors, the fibronectin receptor integrin α5β1 plays a pivotal role in this process. Using a highly specific integrin α5β1 peptidomimetic combined with nanopatterned hydrogels, we show that keratinocyte sheets regulate their migration ability at an optimal integrin α5β1 nanospacing. This efficiency relies on the effective propagation of stresses within the cell monolayer independent of substrate stiffness. For the first time, this work highlights the importance of extracellular matrix receptor nanoscale organization required for efficient tissue regeneration.